Straw application and soil organic carbon change: A meta-analysis - Qiuju Wang; Xin Liu; Jingyang Li; Xiaoyu Yang; Zhenhua Guo (Soil and Water Research, 2021)
Straw return is considered an effective way to improve the soil organic carbon (SOC) content of farmland. Most studies have suggested that a straw application increases the SOC content; however, some suggest that a straw application reduces the SOC content when used in combination with mineral fertilisation. Therefore, a meta-analysis of the effect of a straw application on the SOC change is needed. This study comprises a meta-analysis of 115 observations from 65 research articles worldwide. Straw applications can significantly increase the proportion of the SOC in the soil. Straw applications caused a significant microbial biomass carbon (MBC) increase in tropical and warm climatic zones. The MBC increase was higher than the SOC increase. For agriculture, the most important soil functions are the maintenance of the crop productivity, the nutrient and water transformation, the biological flora and activity, and the maintenance of the microbial abundance and activity. These functions should be prioritised in order to maintain the SOC function and services. Straw applications should not be excessive, especially when combined with mineral fertilisation, in order to avoid the loss of carbon from the straw in the form of greenhouse gases. A large amount of unused fertiliser also leads to a series of environmental problems.